Mobile-based PhilNITS reviewer design: Its functionality, reliability, usability and efficiency - Archolito V. Pahuriray; Rolan O. Algara (Northern Negros State College of Science and Technology (NONESCOST), 2021)
The examination is used to determine the strengths and limitations of certain individuals. In the fast-growing Information Technology (IT) business, IT workers who have certifications on their resumes are more likely to be employed, earn higher salaries, develop their professions, and have more opportunities for new jobs. As mobile devices have become more essential, the need for new applications that can assist teaching and learn on mobile platforms has grown. In the 21st century, mobile learning has a significant impact on education. Incorporating the most recent development technology in review materials proved to be beneficial especially for examinees. Hence, the researchers were immensely motivated to design a mobile-based PhilNITS reviewer. The development of this application can help students broaden their knowledge and evaluate their readiness to take the examination. The development method was adopted as the research design of the study. The developed mobile application is user-friendly and can be accessed offline. Quality in the use model ISO/IEC 25010:2011 was utilized to establish the five evaluation criteria. Results revealed that the mobile-based PhilNITS reviewer is usable and meets its expected functions in terms of functional suitability, performance efficiency, usability, maintainability, and portability. This application will widen the knowledge and examine the individual skills in the field of information technology, especially in mobile development. For further improvement, the researcher recommends that future studies incorporate a top score module with multiple levels to assess and improve the user's understanding of different Information Technology terminology.